Implementasi Metode Show and Tell untuk Mengembangkan Percaya Diri dan Kemandirian Siswa PAUD di Kanaan Global School Jakarta - Yeppy Sihotang (Syntax Corporation Indonesia, 2024)
The background of this study is based on the low self-confidence and independence of students in Kindergarten B class at Kanaan Global School in Jakarta. The purpose of this study is to analyze the differences in self-confidence and differences in independence owned by students after being given the treatment of the show-and-tell method. This study was conducted for four meetings with a total of 17 students in kindergarten B class. This study used a quantitative approach with the One Group Pretest - post-test design. The data from the research was obtained through a rubric assessment of each variable that had been tested for validity and reliability previously. The results of the hypothesis on both variables using the t-test showed a value of 0.000 smaller than 0.005 on self-confidence and independence. The n-gain value of the self-confidence variable is 0.4 and independence is 0.6. So, it shows that there is a difference in self-confidence and independence before and after the implementation of the show-and-tell method on students.